Growing Tomorrow's Teachers Together: The CaBan Initial Teacher Education Partnership. (1st March 2020) - Griffiths, Jeremy; Bamber, Sally; French, Graham; Hulse, Bethan; Jones, Gwyn; Jones, Rhys; Jones, Susan; Williams, Gwawr Maelor; Wordsworth, Hazel; Hughes, J. Carl
In this paper we outline the philosophy and research foundations underpinning the development of CaBan – an Initial Teacher Education (ITE) Partnership developed for the purpose of educating the teachers of tomorrow for North Wales. CaBan represents an ambitious 'learning partnership' of five partners consisting of regional schools, Bangor University, University of Chester, the regional school improvement service (GwE), and the Collaborative Institute for Education Research, Evidence and Impact (CIEREI). Each partner plays a key role in fulfilling our ambitions to contribute to Our National Mission and achieve our vision of 'Growing Tomorrow's Teachers Together.' At its core, the goal of CaBan is to support our new Associate Teachers (ATs) to become creative, inspiring and highly skilled teachers who will contribute to the delivery of A curriculum for Wales – a curriculum for life (Welsh Government, 2015). In this paper we outline: (i) our basic vision and mission as a learning partnership; (ii) the evidence to support our strategic pedagogical position with respect to growing tomorrow's teachers; (iii) the crucial role of mentoring in the development of our ATs as critically reflective practitioners; (iv) how we integrate research as a fundamental element of all we do; (v) how our programme design is underpinned by the notion of professional enquiry and career long professional learning (vi) the specific modes of learning that help nurture ATs' sense of their 'teaching self '; and crucially (vii) the importance of Welsh culture and the Welsh language in education and the role the CaBan partnership has in building capacity to help realise Welsh Government's vision for a million Welsh speakers by 2050.